2011
DOI: 10.1126/science.1208248
|View full text |Cite
|
Sign up to set email alerts
|

GRK2-Dependent S1PR1 Desensitization Is Required for Lymphocytes to Overcome Their Attraction to Blood

Abstract: Lymphocytes egress from lymphoid organs in response to sphingosine-1-phosphate (S1P); minutes later they migrate from blood into tissue against the S1P gradient. The mechanisms facilitating cell movement against the gradient have not been defined. Here we show that G-protein coupled receptor kinase-2 (GRK2) functions in down-regulation of S1P receptor-1 (S1PR1) on blood-exposed lymphocytes. T- and B-cell movement from blood into lymph nodes is reduced in the absence of GRK2 but is restored in S1P-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
186
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(203 citation statements)
references
References 35 publications
14
186
1
2
Order By: Relevance
“…MZ B cells express the S1P receptors S1P 1 and S1P 3 highly, facilitating their S1P‐mediated attraction to the MZ 2, 3, 25. Continual S1P stimulation is required to retain MZ B cells in the MZ and it is the desensitization of S1P receptors on MZ B cells that enables them to overcome their attraction towards S1P in the blood30 and migrate into the follicles. Stromal cells, including FDC, within the B‐cell follicles express CXCL13,31 which stimulates the attraction of CXCR5‐expressing B cells towards the follicles 2, 3, 25, 32.…”
Section: Discussionmentioning
confidence: 99%
“…MZ B cells express the S1P receptors S1P 1 and S1P 3 highly, facilitating their S1P‐mediated attraction to the MZ 2, 3, 25. Continual S1P stimulation is required to retain MZ B cells in the MZ and it is the desensitization of S1P receptors on MZ B cells that enables them to overcome their attraction towards S1P in the blood30 and migrate into the follicles. Stromal cells, including FDC, within the B‐cell follicles express CXCL13,31 which stimulates the attraction of CXCR5‐expressing B cells towards the follicles 2, 3, 25, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene involved in angiogenesis and endothelial cell differentiation is S1PR1 (sphingosine 1-phosphate receptor 1) which is one of the five G protein-coupled receptors for S1P1 (23). Previous studies have suggested that S1PR1 is required for stabilization of nascent blood vessels during embryonic development (24).…”
Section: Discussionmentioning
confidence: 99%
“…An S1P concentration gradient could in principle be created through secretion via S1P transporters such as Spinster2 [52], by HLMVEC-mediated depletion of S1P from the media, or both. S1P is a known chemoattractant for a variety of cell types [28,31,32,53,54]. Furthermore, activation of S1PR1 by S1P promotes lymphangiogenesis via Gai-dependent signalling [33].…”
Section: Cs-l15mentioning
confidence: 99%
“…The concentration of S1P is negligible in interstitial fluid, but is ca. 100 nM in blood and lymphatic fluid [28]. Because of this, the local concentration of S1P provides an important cue in the context of immunological function, lymphangiogenesis and blood vessel stabilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation